Flying High with Mathematics (Journal of Parents and Teachers, 2018)
As if they were talking about a flight, Pablo and Clara, two students of Primary Education at Universidad Pontifica Comillas, tell us their learning process in relation with the Mathematics` teaching. They try to underline the most important aspects for them in relation with a good teaching and a valuable learning process. In addition, they share with the readers different learning experiences they have lived during their degree.
Keywords: mathematics; manipulative learning; pre-service teachers; interdisciplinarity